2020
DOI: 10.3390/su12198073
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Review of Cruise Service Quality: Case Studies from Asia

Abstract: Although the cruise sector is considered an ‘unreplaceable’ form of tourism, with the cruise industry recording steady growth over the years, there is a lack of research and analysis on cruise ships themselves. Accordingly, this study sought to determine whether service quality differences among ships operating in the Asian market could suggest broader implications for the sustainability of the cruise industry. We chose the SERVQUAL framework for the analysis; we also employed the multiple case study method an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
0
13
0
4
Order By: Relevance
“…In the results of this work, it is observed that trust is an element as fundamental as satisfaction or more. In addition, the feeling that the organisation is doing its best to satisfy the needs, affects the happiness of the athlete as much or more than the positive feeling derived from this relationship (Yoon and Cha, 2020). This is because it is the variable from which the entire model starts and which has very strong connections with all the variables, whether direct or indirect.…”
Section: Discussionmentioning
confidence: 99%
“…In the results of this work, it is observed that trust is an element as fundamental as satisfaction or more. In addition, the feeling that the organisation is doing its best to satisfy the needs, affects the happiness of the athlete as much or more than the positive feeling derived from this relationship (Yoon and Cha, 2020). This is because it is the variable from which the entire model starts and which has very strong connections with all the variables, whether direct or indirect.…”
Section: Discussionmentioning
confidence: 99%
“…On cruise ships, SA technologies not only transfer responsibility from crew members to passengers but also help to reduce waiting times, minimize service errors and improve the overall passenger experience . For example, digital self-service kiosks/tablets enable cruise passengers to complete tasks independently, improving responsiveness and reducing peak-hour wait time (Yoon and Cha, 2020).…”
Section: Service Automation Technologies Onboard Cruise Shipsmentioning
confidence: 99%
“…Moreover, it is essential for customers’ evaluation of the overall cruise service. Interaction can be measured according to assurance, responsiveness, reliability, and empathy during cruise service delivery [ 34 ]. The outcome refers to the utility of onboard attributes that cruise trips bring to customers, which is a determining factor for customer decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%